Predicting procedural justice in police-citizen encounters - Mastrofski, Stephen D. (Criminal justice and behavior, 2016)
Police exercise great discretion in their dealings with the public, but most research on police discretion focuses on coercive decisions. Despite the demonstrated importance of procedural justice (PJ) for police legitimacy and overall satisfaction, the predictors of police-provided PJ in police?citizen encounters have rarely been examined. We propose a framework for assessing the choice of police officers to engage in PJ and test it using data collected in direct observations of police interactions with the public. We find significant effects for the moral ?worthiness? of the citizen as reflected in his or her role in the situation; for situational challenges of engaging in PJ, including large audience and officer mental/emotional fatigue; and for popular scripts for handling traffic-related encounters and serving in a backup role. We interpret and discuss the implications of our findings and suggest avenues for advancing understanding of the factors underlying procedurally just police treatment.